Absenteeism and Overtime: Double Jeopardy - Mikalachki, Al; Chapple, D. (Relations industrielles / Industrial Relations, 1977)
This study investigated factors leading to absenteeism in a large auto plant employing about 1,000 workers. The hypotheses examined dealt with the effect on absenteeism of: the skill required for the job, the worker's age and health, and the base pay rate. The initial analysis proved opposite of what is usually found. An additional factor was examined: the ability of the worker to control the amount of overtime he worked. The data then showed that the worker who is able to achieve a set income for the fewest days in attendance by working overtime, uses this device to spend less time on the job. Ideas were also presented to show that positive reinforcement of good attendance can result in decreased absenteeism.